PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PENGGUNA JASA PADA PT. POS INDONESIA CABANG PANDAN - Megawati, Megawati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The results showed a positive relationship between service quality and performance at PT. Pos Indonesia Pandan Branch of Tapanuli Tengahi Regency is 0.949, so if interpreted on a scale the value can be categorized high. The regression equation obtained Y = 10.351 + 0.718X which shows the effect of service quality on the level of service user satisfaction. The t test showed that the hypothesis was accepted to be correct, where t arithmetic 6.056> t table 2.04227, which means that the level of service user satisfaction would increase by a regression coefficient / slop (0.718) if the service quality variable was added by one unit. While the coefficient of determination is known that the quality of service only contributes 55% to the level of service user satisfaction at PT. Pos Indonesia Pandan Branch and the remaining 45% is influenced by other factors not examined.